1996
DOI: 10.1007/bf02369734
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and identification of heat- and mass-transfer processes in intumescent heat-insulating materials

Abstract: The development and use of intumescent heat-insulating materials is important for ensuring fire safety and refractoriness of various structures exposed to powerful sources of heat energy [1][2][3][4][5]. Under heat loading such materials can increase in thickness by a factor of greater than several tens [3][4][5], forming a heat-insulating layer with a low thermal conductivity and thereby protecting the wall of the structure against damage. The number of such materials and the cost of thermal tests for their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…On the basis of the experimental [7,8] and evaluated theoretical results [9,11], a corrected formulation of the problem on stoichiometric destruction of a multilayer heat shield material has been obtained. To obtain reliable theoretical results, it is necessary to take into account the specifi city of the internal structure of the BRFC under heating: the heat release by thermal decomposition and the heat fl ow across the tablet.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of the experimental [7,8] and evaluated theoretical results [9,11], a corrected formulation of the problem on stoichiometric destruction of a multilayer heat shield material has been obtained. To obtain reliable theoretical results, it is necessary to take into account the specifi city of the internal structure of the BRFC under heating: the heat release by thermal decomposition and the heat fl ow across the tablet.…”
Section: Discussionmentioning
confidence: 99%
“…In [9,11], it was shown that such a process of BFRC destruction corresponds with good accuracy to the real process. However, in the present paper, as opposed to [9,11], the heat propagation by conduction along the transverse coordinate r is taken into account [8]. Such account is also taken in modeling the heat and mass transfer in the wood [12] and the substrate.…”
mentioning
confidence: 99%
See 3 more Smart Citations